Mortality from cervical cancer in brazilian regions: An ecological study (Research, Society and Development, 2024)
Introduction Cervical cancer is the fourth most common cancer among women globally. Objective: To analyze mortality from cervical cancer (CC) in brazilian regions. Methods: A cross-sectional, descriptive and quantitative study, using data from the Mortality Information System (SIM/SUS), linked to DATASUS, analyzing number of deaths from CC in Brazilian regions, from 2015 to 2023, covering women aged between 20 and 80 years. Descriptive statistics were applied using Microsoft Office Excel. The analysis included calculation of mortality rates based on the population estimated by the Brazilian Institute of Geography and Statistics (IBGE) and using ICD-10 to classify the neoplasm. Results: Between 2015 and 2021, there were 44,292 deaths in Brazil, with the North and Northeast regions showing the highest mortality rates. The 50-59 age group recorded the highest frequency of mortality. As for color/race, the North (74.8%), Northeast (66.20%) and Midwest (52.43%) regions recorded more deaths among brown women, while the South (81.56%) and Southeast (51.56%) white women predominated. Most of the women were single and had low levels of schooling, especially in the Northeast and Southeast. Conclusion: The data indicate an increase in the mortality rate between 2015 and 2018, followed by a reduction after 2018. This study has limitations, such as underreporting of deaths and the inability to establish causal associations. Therefore, there is a need for further research to understand the decrease in the mortality rate after 2018, and for health promotion policies to expand the coverage of cytopathological examination.